N-doped TiO2 nanotube arrays with mixed phase for enhanced photocathodic protection of 304 stainless steel under visible light. (November 2022) - Zhang, Tingting; Ni, Anqi; Xu, Yuqing; Fu, Danni; Lin, Peng
Abstract: Effective N-doped TiO2 nanotube arrays with rutile–anatase mixed phase were fabricated by two-step anodization method and annealing in a NH3 atmosphere. Compared with pure anatase TiO2 nanotube arrays, the photocurrent density of N-doped TiO2 nanotube arrays with mixed phase increased by about three times under visible light. Moreover, the open circuit potential of 304 stainless steel obviously negatively shifted when coupled with N-doped TiO2 nanotube arrays with mixed phase under visible light. The enhancement was mainly because N-doping extends light absorbance and the mixed phase is beneficial for the separation of photoexcited electrons–holes. Therefore, N-doped TiO2 nanotube arrays with mixed phase showed highly effective photogenerated cathodic protection of 304 stainless steel under visible light. Interestingly, the photoelectrode also displayed a cathodic protection effect after removing irradiation, which is meaningful for practical applications. Graphical abstract: Compared with pure anatase TiO2 nanotubes array, the photocurrent density of N-m- TNT increases by about 3 times under visible light and show highly effective photogenerated cathodic protection of 304 stainless steel in 3.5 wt% NaCl solution under visible light illumination. Image 1 Highlights: N-doped TiO2 nanotube arrays with anatase/rutile mixed phase were successfully fabricated by annealing at NH3 atmosphere. The composite photoanode exhibits visible light absorbance and enhanced charge separation efficiency. The composite photoelectrode shows enhanced photoelectricity response under solar light (1 sun) and visible light. The composite photoelectrode shows effective photogenerated cathodic protection of 304 stainless steel under visible light.